Changes in the oxidative-antioxidant status of blood in freestyle wrestlers under the influence of physical exertion - N. A. Kurashova; A. A. Yureva; I. N. Gutnik; L. A. Grebenkina; A. V. Labygina; L. I. Kolesnikova (Спортивная медицина: наука и практика)
Purpose of the study: to evaluate the “lipid peroxidation-antioxidant protection” system in freestyle wrestlers under the influence of intense physical activity in order to identify the nature of oxidative processes and the antioxidant status of the athletes’ body.Materials and methods: the study involved athletes — freestyle wrestlers, boys 18–22 years old, with sports qualifications: candidate master of sports or master of sports, regularly involved in freestyle wrestling. The control group consisted of students who did not have a sports category and were not involved in sports activities, comparable in gender, age, weight category with the comparison group.  The material for the study was plasma and red blood cells. Blood sampling from athletes was carried out twice, at the end of the preparatory and competitive periods, in the morning, on an empty stomach from the ulnar vein, in accordance with generally accepted requirements. Components of lipid peroxidation and antioxidant defense were determined using spectrophotometric and fluorometric methods.Results: it was found that in athletes after intense physical activity (competitive period), there is a significantly significant decrease in substrates with double bonds by 61 %, primary products by 59 % and intermediate products by 44 %, an increase in the final products of lipid peroxidation by 25 % against the background of inhibition activity of antioxidant protection components: retinol by 40 %, superoxide dismutase by 7 % and reduced glutathione by 11 %.Conclusion: The level of free radical processes increases during physical activity due to the accumulation of oxygen in organs and tissues, and depends on the intensity and duration of the exercise. In the course of the study, it was established that the preparatory and competitive periods, in comparison with the control group, among freestyle wrestlers, depending on the previous level of physical activity, are characterized by activation of lipid peroxidation processes and inhibition of enzymatic and non-enzymatic components of antioxidant protection. The established changes are recommended to be taken into account when conducting comprehensive rehabilitation of athletes, when developing recommendations for improving the training process, as well as when using antioxidant complexes for athletes aimed at restoring various parts of the body’s antioxidant defense.